PARAMETRIC STATISTICS ANALYSIS OF HEALTH RESEARCH USING SPSS 17.0 AND EXCELL - Siti Nurhabibah Hutagalung (INFOKUM, 2021)
The health sector data survey on data variables randomly for data greater than 100 was tested for several hypotheses with significant values. >0.05, the effectiveness of using SPSS 17.00 and Microsoft Office on the feature settings used. The normality test on the data distribution is adjusted to the limit value for each test. The data input discrepancy is influenced by the significant value and the limit value. Hypothesis testing performs a comparison between the sample value and the proposed hypothesis value. The conclusions that can be drawn from hypothesis testing are rejecting the null hypothesis and failing to reject it. the value of = 0.05 (5%) for health/social research and = 0.01 (10%) for laboratory research